Allopregnanolone in Postpartum Depression - Pinna, Graziano; Almeida, Felipe B.; Davis, John M. (Frontiers in Global Women's Health, 2022)
Postpartum depression (PPD) is a debilitating psychiatric disorder characterized by a high worldwide prevalence and serious long-term negative outcomes for both mothers and children. The lack of a specific treatment and overreliance on pharmacotherapy with limited efficacy and delayed treatment response has constituted a complication in the management of PPD. Recently, the Food and Drug Administration (FDA) in the USA approved a synthetic formulation of the GABAergic neurosteroid allopregnanolone, administered intravenously (brexanolone) for the rapid, long-lasting and effective treatment of PPD. Hereinafter, we review findings on allopregnanolone biosynthesis and GABAA receptor plasticity in the pathophysiology of PPD. We also discuss evidence supporting the efficacy of brexanolone for the treatment of PPD, which opens a promising new horizon for neurosteroid-based therapeutics for mood disorders.